FIXED PARTIAL DENTURE TREATMENT IN THE CASE OF EXTRUDED ANTAGONISTIC TEETH: CASE REPORT - Bakhtiar, Dika Agung; Aslamiyah, Qonitah Nur (Universitas Muhammadiyah Semarang, 2025)
Background: Permanent first molar teeth are the key to determining occlusion in dental development. One of the consequences of lower first molar tooth loss is upper first molar tooth extrusion. Tooth loss leads to structural changes in the dental arch, so replacing the missing teeth as soon as possible is important. This can be achieved with the help of a fixed partial denture.Case: A 21-year-old female patient came to the Prosthodontic Department of UNIMUS RSGMP in May 2024, complaining of discomfort and chewing food difficulty, the patient also felt that her upper molars began to look elongated. The treatment results showed no complaints, good retention, stabilization and occlusion of the fixed partial denture.Conclusion: Fixed partial denture treatment with hygienic pontic in cases of extruded antagonistic teeth shows a good level of treatment success characterized by the absence of complaints of either a sense of blocking when chewing food or speaking, no signs of inflammation or trauma as well as good retention, stabilization, and occlusion of the fixed partial denture.